Tangible Heritage: Production of Astrolabes on a Laser Engraver - Zotti, G. (Computer graphics forum, 2008)
The astrolabe, an analog computing device, used to be the iconic instrument of astronomers during the Middle Ages. It allowed a multitude of operations of practical astronomy which were otherwise cumbersome to perform in an epoch when mathematics had apparently almost been forgotten. Usually made from wood or sheet metal, a few hundred instruments, mostly from brass, survived until today and are valuable museum showpieces. This paper explains a procedural modelling approach for the construction of the classical kinds of astrolabes, which allows a wide variety of applications from plain explanatory illustrations to three‐dimensional (3D) models, and even the production of working physical astrolabes usable for public or classroom demonstrations.